6.3 million euros were allocated to increase the adoption of silvopastoral systems and sustainable technologies in the Colombian Amazon region - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Within the framework of the Development Programs with a Territorial Approach (PDET) Routes for Stabilization, program of the European Fund for Peace, 6.3 million euros in financing was obtained. The livestock component will benefit 370 production units (farms), 560 hectares and 540 mainly small and medium-sized producers. CGIAR innovations key for the achievement of this outcome were based on the research on silvopastoral systems, environmental and economic benefits, in terms of biodiversity, soil health, forage quality, income, and livelihoods.